2018
DOI: 10.1002/14651858.cd005061.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-glucosidase inhibitors for prevention or delay of type 2 diabetes mellitus and its associated complications in people at increased risk of developing type 2 diabetes mellitus

Abstract: Alpha-glucosidase inhibitors for prevention or delay of type 2 diabetes mellitus and its associated complications in people at increased risk of developing type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 88 publications
0
29
0
Order By: Relevance
“…Another important pathway involved in carbohydrate metabolism is α-glucosidase enzyme, which converts disaccharides into monosaccharides at the cells lining the intestine. In diabetic patients, the short-term effect of these drugs therapies is to decrease current blood glucose levels [26]. GG03 and GD did not inhibit α-glucosidase.…”
Section: Discussionmentioning
confidence: 99%
“…Another important pathway involved in carbohydrate metabolism is α-glucosidase enzyme, which converts disaccharides into monosaccharides at the cells lining the intestine. In diabetic patients, the short-term effect of these drugs therapies is to decrease current blood glucose levels [26]. GG03 and GD did not inhibit α-glucosidase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although there are no unified views [ 21 , 22 , 23 ], it has been reported that long-term acarbose treatments improve insulin sensitivity [ 22 , 23 ] and secretion [ 23 ]. The efficacy of α -glucosidase inhibitors for preventing or delaying the onset of type 2 diabetes had been suggested in individuals with impaired glucose tolerance (IGT) and those at an increased risk for diabetes [ 24 ]. Therefore, the HPGA natto may also contribute to the prevention of IGT and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This means the alpha-glucosidase complexes are competitively inhibited and their availability to oligosaccharides from dietary starch is reduced. Thus, monosaccharide formation decreases and less insulin is required to metabolize glucose, leading to a reduction of food induced increases in blood glucose and insulin (Moelands et al, 2018).…”
Section: Current T2dm Drug Treatments In New Zealandmentioning
confidence: 99%